Report on the international workshop "Regional Socio-Economic Processes in Central and Eastern Europe - 20 Years in Transition and 2 Years in Global Economic Crisis" - Erőss, Ágnes; Karácsonyi, Dávid (Hungarian Geographical Bulletin, 2011)
-